Taxonomic remarks on Scilla anthericoides Poir. (Asparagaceae, Scilloideae), a neglected species from Algeria - Vela, Errol; de Bélair, Gérard; Rosato, Marcela; Rosselló, Josep (Phytotaxa, 2016)
Scilla anthericoides is a neglected name traditionally considered as Urginea maritima var. anthericoides. Based on recent field observations of living plants completed by karyological analyses, we promote again this taxon at species rank, under the genus Charybdis. It differs from other species of Charybdis maritima aggregate by many characters of flowers, fruits, bulbs, leaves and by ploidy level. It is endemic to the regional hotspot Kabylias-Numidia-Kroumiria in north-eastern Algeria. It is a threatened species that has been assessed as vulnerable.